Curbing credit corruption in China: The role of FinTech - Fan Su; Chao Xu (Journal of Innovation & Knowledge (JIK), 2023)
FinTech is an emerging financial innovation model that promotes a 'technological anti-corruption' effect. Credit corruption is a worldwide problem; however, previous studies have not focused on the anti-corruption effect of FinTech. This study first uses micro data from FinTech companies to construct city-level FinTech measurement indicators in China. An objective measurement of credit corruption is then formed by separating the expenditures for credit corruption from total business entertainment expenses. This study empirically explores the impact of FinTech on credit corruption using a sample of Chinese listed companies on the Shanghai and Shenzhen stock exchanges from 2011 to 2019. The results show that FinTech can significantly curb credit corruption, and that the expenditures for credit corruption of local companies are lower with better regional FinTech. These findings are valid after addressing endogeneity issues and conducting a series of robustness tests. The results of the heterogeneity test show that FinTech offers greater advantages for risk identification, information mining, and inclusive development than traditional finance. The curbing effect on credit corruption is stronger in companies with better intrinsic quality, more transparent information disclosure, located in less financially developed and more corrupt regions. Economic consequence analysis suggests that FinTech can correct resource misallocation caused by credit corruption and promote corporate investment efficiency. These findings are valuable for policy practices for technological anti-corruption in the financial sector.
Keywords: G21; G31; O33; 650; Credit corruption; Digital and intelligent transformation in banks; FinTech; Technological anti-corruption